The Innovative Role of Entrepreneurship Courses in Shaping The Entrepreneurial Mindset of Generation Z: A Systematic Literature Review - Syafitri, Dinda; Wardani, Anita Kusuma; S, Sudarmiatin; Zanky, Mukhammad Nuruddin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The purpose of this study is to analyze innovative business practices in fostering an entrepreneurial mindset among Generation Z thru a Systematic Literature Review (SLR). 16 scholarly articles from Google Scholar published between 2020 and 2025 are examined. The literature selection process adheres to the PRISMA guidelines, which encompass the study question, literature review, inclusion and exclusion criteria, quality assessment (QA1–QA3), data collection, and results. The analysis results show that college entrepreneurship has a significant impact on the development of Generation Z students' entrepreneurial mindset thru project-based learning and experiential learning. The type of educational innovation that has the greatest impact on the development of Generation Z businesses includes industry collaboration, mentorship practices, and the integration of digital technology into the learning process. In addition, the success of entrepreneurship education for Generation Z is greatly influenced by collaborative campus environments, access to business incubators, and the use of digital platforms as concept exploration media. The results of this study indicate that the development of the Entrepreneurship course must be based on an application-based, technologically adaptive, and real-world-oriented learning paradigm in order to foster an entrepreneurial attitude.